UNIVERSITY-LEVEL STUDENTS’ DIFFICULTIES IN DESCRIPTIVE WRITING - Maya Marsevani; Yeo, Frisca; Nurlaily (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
While most studies have focused on the challenges faced by high school students in writing descriptive or recount texts, limited research has examined the difficulties encountered by university students, particularly those with low motivation and insufficient grammar proficiency. This study aims to investigate the specific challenges faced by university-level students majoring in English when composing descriptive texts. Using a qualitative descriptive approach, data were collected through a questionnaire distributed via Google Forms and a descriptive writing test. The findings reveal that grammar is the most significant challenge, with the lowest average score of 69.3 among five assessed categories. Common errors include incorrect tense usage and word choice, leading to unclear or unintended meanings. These findings highlight the need for targeted instructional strategies to enhance students' grammatical competence and overall writing proficiency.